Tekstilkunst i Danmark : 1960-87 - Graae, Annette; Kornerup, Ann Mari; Nevers, Jette; Ørom, Anette (Borgen : Billedkunstnerne Forbund, 1987)
Agger, Margarete ; Andersen, Birgit ; Balle, Grete ; Balsgaard, Jane ; Baslund, Helle ; Berntsen, Risse ; Bidstrup, Lena ; Mollengaard Birch, Jytte ; Birckner, Mette ; Chrom Birk, Margit ; Bjorn, Anne ; Bohn, Kirsten ; et al.
boek